1997
DOI: 10.1079/bjn19970197
|View full text |Cite
|
Sign up to set email alerts
|

Influences of dietary methionine and cysteine on metabolic responses to immunological stress byEscherichia colilipopolysaccharide injection, and mitogenic response in broiler chickens

Abstract: The present experiments were conducted to investigate influences of dietary methionine and cysteine on metabolic responses to immunological stress induced by Escherichia coli lipopolysaccharide (LPS) injection, and concanavalin A (Con A)-induced mononuclear cell (MNC) proliferation in male broiler chickens. In Expt 1, chicks (12 d of age) were fed on a S amino acid (SAA)-deficient diet (5.6 g S A M g diet) or on three kinds of SAA-sufficient diet (9.3 g SAAkg diet; low-, medium-and high-cysteine diets) which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Cellular immunity which measured by heterophil to lymphocyte ratios, and CBH responses was not affected by dietary levels of methionine. The results were in agreement with the finding of Dabbert et al (1996) that showed methionine did not change wing-web PHA response in adult quail or the Con A-induced proliferative response of thymus mononuclear cells (Takahashi et al, 1997). In the contrary, cutaneous wing-web or wattle response to PHA in young broiler chickens were enhanced (Tsiagbe et al, 1987;Rama Rao et al, 2003) while heterophil to lymphocyte ratios was not affected by methionine levels (Rama Rao et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Cellular immunity which measured by heterophil to lymphocyte ratios, and CBH responses was not affected by dietary levels of methionine. The results were in agreement with the finding of Dabbert et al (1996) that showed methionine did not change wing-web PHA response in adult quail or the Con A-induced proliferative response of thymus mononuclear cells (Takahashi et al, 1997). In the contrary, cutaneous wing-web or wattle response to PHA in young broiler chickens were enhanced (Tsiagbe et al, 1987;Rama Rao et al, 2003) while heterophil to lymphocyte ratios was not affected by methionine levels (Rama Rao et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…It was discovered due to its binding to the C-polysaccharide of 1999) and birds after lipopolysaccharide (LPS), turpentine and croton oil studies in domestic fowl (Patterson and Mora, 1964;1965;Hallquist and Klasing, 1994;Tohjo et al, 1995;Takahashi et al, 1997;Nakamura et al, 1998;Chamanza et al, 1999a;Adler et al, 2001;Xie et al, 2002;Upragarin, 2005) and LPS and haemorrhagic enteritis virus investigations in turkey (Mazur-Gonkowska et al, 2004). For avian cytokines the reader is referred to (Lynagh et al, 2000;Sijben et al, 2003;Leshchinsky and Klasing, 2003;Abdalla et al, 2004;Kaiser et al, 2004;2005) pneumococci.…”
Section: Function Of Positive Acute Phase Proteinsmentioning
confidence: 99%
“…For ruminants, the amino acid composition of MP is still uncertain and, at present, there is only limited information available on the amino acid composition of proteins involved in the expression of immunity. For example, it has been suggested that immune cells have a relatively high requirement for glutamine (Calder, 1995) and for cysteine and methionine (MacRae, 1993;Takahashi et al 1997;Dröge & Breitkreutz, 2000). Likewise, a relatively large amount of phenylalanine and tryptophan is required for the acute-phase protein response which is usually associated with responses to systemic infections or trauma (Reeds et al 1994).…”
Section: Metabolisable Protein Requirement For Expression Of Immunitymentioning
confidence: 99%